Synergistic activity of dispersin B and benzoyl peroxide against Cutibacterium acnes/Staphylococcus epidermidis dual-species biofilms - Jeffrey B. Kaplan; Anna Muzaleva; Miloslav Sailer; Robert B. Huizinga; Khalaf Kridin (PLoS ONE, 2025)
Cutibacterium acnes plays a key role in the development of acne vulgaris, with biofilm formation contributing to its persistence and resistance to antimicrobial treatments. A critical component of C. acnes biofilms is poly-N-acetylglucosamine (PNAG), an exopolysaccharide that facilitates both biofilm stability and biocide resistance. This study evaluated the efficacy of the PNAG-degrading enzyme dispersin B in enhancing the susceptibility of C. acnes biofilms to benzoyl peroxide (BP), a common anti-acne agent. Dual-species biofilms of C. acnes and Staphylococcus epidermidis, which has been shown to promote C. acnes biofilm growth under aerobic conditions, were cultivated in glass tubes and treated with dispersin B (5–80 µg/mL), BP (0.1–2.5%), or a combination of both. Dispersin B or BP alone reduced C. acnes colony-forming units (CFUs) by 1–2 log units. However, sequential treatment with dispersin B followed by BP achieved a synergistic effect, yielding a >6-log reduction in CFUs. Remarkably, concentrations as low as 5 µg/mL dispersin B combined with 0.5% BP efficiently eradicated C. acnes from the dual-species biofilms. These findings highlight the protective role of PNAG against BP and demonstrate the potential of dispersin B as an adjunctive therapy to enhance the efficacy of BP in acne treatment.